Syntactical means of dialogical organizing of scientific-educational texts (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The principal syntactical means implementing cognitive function, making communicative effect of internal speech dialogicity, increasing scientific-educational text informativity and tending to language redundancy reduction, ensuring adequate perlocutive effect are pointed out and characterized in the article.
Keywords: an author; an addressee; syntactical means of dialogical organizing; a scientific-educational text